FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PENGUNGKAPAN TANGGUNGJAWAB SOSIAL DAN LINGKUNGAN PERUSAHAAN - Wulansari, Devita Dwi Septi; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the influence of leverage, companyâs profitability, firm size, the size board of commissioner ownership, managerial ownership, and institutional ownership to the disclosure of corporate social responsibility. The result of the analysis show that leverage and firm size has significant influence to the corporate social responsibility. Meanwhile, companyâs profitability, the size board of commissioner ownership, managerial ownership, and institutional ownership do not have any influence to the corporate social responsibility.Keywords: leverage, companyâs profitability, firm size, the size board of commissioner ownership, institutional ownership